Professional negligence in torts a study of on architects, engineers, building contractors and surveyors / Ruzita Khalid - Khalid, Ruzita (Faculty of Law, 1987)
English Common Law formed part of the laws in Malaysia. The authority for the reception of this law of England into this country is provided under Section 3 of the Civil Law Act 1959 (Revised 1972). The statute also provided for the limitation of time period for the application of this law. As regards Peninsular Malaysia the date 7th April 1956. Sabah, 1st December 1951 and in Sarawak, 12th December 1949 is significant because only English Common Law and equity as administered on the date is applicable. However in spite of the limitation of time period English Common Law particularly in torts is still followed in Malaysia. This can be seen from some of the decided cases mentioned in this paper. In order to bring the law into line with the modern day trend several changes have been introduced through judicial decisions. An examination on cases of professional negligence shows that prior to 19605, the courts have been reluctance to award damages for pure financial lose. In 1962 with the decision in Hedley Byrne's case the liability had been widened. This case has opened the way for the recognition of new-duty situations where pecuniary loss is involved.